Impact of intermittent fasting on physical activity: a national survey of Chinese residents aged 18–80 years - He, Feiying; Bai, Shiyu; Xu, Xiangchun; Miao, Jingqiao; Yu, Hongwen; Qiu, Jiale; Wu, Yibo; Fan, Yangdong; Shi, Lei (Frontiers in Physiology, 2025)
ObjectivesThis study aims to investigate the prevalence of intermittent fasting (IF) among Chinese residents aged 18–80 and assess its impact on physical activity (PA) levels.MethodsData were sourced from the Psychology and Behavior Investigation of Chinese Residents, a nationally representative cross-sectional survey conducted between June 20 and 31 August 2022. A multistage stratified cluster sampling method was used. Propensity score matching (PSM) was applied to compare PA levels between individuals practicing IF and those not practicing it. Multiple logistic regression and subgroup analysis were performed to explore associations between PA levels and relevant factors.ResultsIF was practiced by 9.78% of participants, with the highest prevalence (70.78%) among those aged 18–34. While there were no significant differences in baseline characteristics between the IF and non-IF groups, sleep duration differed. IF was significantly associated with reduced PA levels (OR = 0.769, 95%CI: 0.657–0.900), and subgroup analysis highlighted the effect of sleep patterns on PA.ConclusionIF is common among younger Chinese residents and correlates with lower PA levels, indicating a potential need for individualized health guidance to balance dietary strategies with PA.